Rancang Bangun Sistem Rekrutmen Online Berbasis Web Menggunakan Metode Prototype pada PT Snapdev Digital Indonesia - Rio Adi Lukmana; Muhammad ASY Syarief AL Hidayatullah; Chairul Anwar (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
The rapid advancement of information technology has encouraged organizations to adopt digital transformation, including in human resource recruitment. PT Snapdev Digital Indonesia requires an effective and efficient recruitment process to attract qualified candidates. However, the existing system faces challenges, including unintegrated applicant data management, delays in the selection process, limited application tracking, and insufficient information transparency. This study aims to analyze the current recruitment process, develop a web-based online recruitment system using the Prototype method, and evaluate its quality based on the ISO/IEC 25010 standard. A mixed-method approach was employed through observation, interviews, documentation, and literature review. The system was designed using Unified Modeling Language (UML) and developed through iterative prototyping, incorporating user feedback during refinement. System quality was evaluated using ISO/IEC 25010 characteristics, including functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability. The results demonstrate that the proposed system improves recruitment efficiency, streamlines applicant data management, accelerates the selection process, and enhances information transparency. Furthermore, the evaluation confirms that the system satisfies user requirements and is suitable for implementation at PT Snapdev Digital Indonesia.